ADOPSI DAN PEMELIHARAAN ANAK DALAM HUKUM ISLAM - MS, Syaifullah; Datumula, Sarfika (Pusat Studi Gender dan Anak, IAIN Palu, 2021)
Adoption of children is one of the noble ways for couples who have not been blessed with children. The presence of an adopted child is expected to fill the lonely days of husband and wife, even sometimes many couples make their adopted children as a